Pre-Injury Driving Records of Trauma Center Patients Relative to Psychoactive Substance Use Disorders, Mode of Injury, and BAC Status - Soderstrom, Carl A. (Association for the Advancement of Automotive Medicine, 1998)
The goal of this study was to assess pre-injury driving convictions (speeding, reckless driving, impaired driving, major license violations) among trauma center patients with respect to psychoactive substance use disorder (PSUD) diagnoses, mode of injury, and blood alcohol concentration (BAC) status at the time of admission. Driving records of 778 patients were linked to PSUDs and BAC. Twenty-nine percent of patients had a conviction in the 3 years prior to injury. Types of violation were not related to mode of injury. Although there was a positive association between prior impaired driving convictions, current alcohol dependence, and BAC+ status, a consistent pattern relative to other pre-injury convictions, PSUDs, and BAC status was not apparent.